(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of entrepreneurship orientation and product innovation on the performance of SMEs assisted by Kadin Jabar in the food industry. The population in this study were 30 SMEs with sampling using the saturated sampling method so that the sample of this study amounted to 30 SMEs. Data were analyzed using multiple regression analysis techniques. The results showed that there was no influence between entrepreneurial orientation on performance, while product innovation had a significant effect on the performance of SMEs, as well as entrepreneurial orientation and product innovation had a simultaneous significant effect on the performance of SMEs assisted by Kadin Jabar in the food industry.